‘One size does not fit all’ : la territorialisation des politiques de l’emploi dans l’Angleterre du New Labour - Corinne Nativel (Revue Française de Civilisation Britannique)
The local management of employment policies is representative of the rhetoric and implementation of New Labour’s “new localism”. The Blairite localism rests upon a networked governance and the operation of partnerships between public, private and voluntary sector organisations. The government is hoping to draw a vast array of benefits for its employment and social inclusion agenda. This article underlines the contradictions and limits of this approach using the examples of welfare-to-work and adult learning. It further stresses that the linkages between various scales of governance in the field of active labour market policy need to receive thoughtful consideration.